Light-emitting device and display device
By adopting the core-shell quantum dot and optimized transport layer design with well-shell structure in QLED light emitting devices, the complex problem of carrier transmission caused by the difference in quantum dot materials is solved, and the luminous efficiency and life are improved, ensuring that Highly efficient carrier recombination and long-lived fluorescence performance.
Patent Information
- Application Number
- CN202310750612.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
QLED light emitting devices have challenges in optimizing luminescence efficiency and lifetime, mainly due to the differences in quantum dot materials, the carrier transmission situation is complicated, making it difficult to improve luminescence efficiency and lifetime at the same time.
Core-shell quantum dots with well-shell structure are used as the luminescent layer material, and are combined with hole transport layer and electron transport layer to ensure efficient injection balance of holes and electrons. A double-layer film structure constructed by setting up a two-layer quantum dot , optimize shell thickness and material selection to improve carrier recombination efficiency.
It significantly improves the luminous efficiency and life, ensures effective injection and efficient recombination of carriers in the device, extends the exciton fluorescence life, reduces the charging probability of the device, and improves the overall performance.
Smart Images

Figure CN119183309A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display, and in particular to a light-emitting device and a display apparatus. Background Art
[0002] Light-emitting devices emit light by releasing energy through the recombination of electrons and holes, and are widely used in the field of lighting. In recent years, quantum dots (QDs) have attracted widespread attention from industry, academia, and research circles due to their advantages of high fluorescence quantum yield, good monochromaticity, continuously adjustable emission spectrum with size, and strong photochemical and thermal stability. Quantum dot light emitting diodes (QLEDs) constructed with quantum dots as the light-emitting layer have become one of the most active scientific research topics due to their many advantages such as low cost, high brightness, wide color gamut, and excellent solution processability, and have shown great competitive potential in the next generation of flat panel display and solid-state lighting applications.
[0003] Although QLED display technology is inherited and developed from OLED (Organic Light-Emitting Diode), the performance of the device can be improved by applying the existing theories in OLED to QLED. However, since quantum dots are nanomaterials, when paired with other functional layers, there are huge differences in the type of material, its own structural design and film quality, the film interface injection barrier between the quantum dot material and other functional layers, and the aging and attenuation of the material itself. As a result, when different quantum dots are used in the actual processing process, completely different carrier transmission conditions will appear in the device, which aggravates the difficulty of optimizing QLED devices, making it difficult to improve the luminous efficiency and life of QLED devices at the same time, greatly limiting its development. Therefore, for quantum dot materials with large differences, it is urgent to develop more targeted high-performance light-emitting devices. Summary of the invention
[0004] In view of this, the present application provides a light-emitting device and a display device, aiming to simultaneously improve the light-emitting efficiency and service life of the light-emitting device.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, the present application provides a light-emitting device, comprising an anode, a hole transport layer, a light-emitting layer, and a cathode, which are sequentially stacked, wherein the material of the light-emitting layer comprises core-shell quantum dots, the core-shell quantum dots comprise a plurality of shell layers, the plurality of shell layers comprise adjacent first shell layers, second shell layers, and third shell layers, wherein the band gap of the material of the second shell layer is smaller than the band gap of the material of the first shell layer, and smaller than the band gap of the material of the third shell layer, and the thickness of the light-emitting layer is 1.6 to 2.3 times the average particle size of the core-shell quantum dots;
[0007] The mobility of the material of the hole transport layer is greater than 10×10 -3 cm 2 / Vs, and less than 100×10 -3 cm 2 / Vs.
[0008] Optionally, in some embodiments of the present application, the fluorescence quantum yield of the core-shell quantum dots is greater than or equal to 70%; and / or,
[0009] The average particle size of the core-shell quantum dots is greater than 8 and less than 11 nm; and / or,
[0010] The material of the first shell layer includes ZnS, the material of the second shell layer includes CdZnS, and the material of the third shell layer includes ZnS; and / or,
[0011] The core-shell quantum dot has a core, and the plurality of shell layers further include an inner shell layer located between the first shell layer and the core, and the material of the inner shell layer includes ZnSe.
[0012] Optionally, in some embodiments of the present application, the ratio of the thickness of the inner shell layer to the radius of the core of the core-shell quantum dot is 0.5 to 2:1; and / or,
[0013] The ratio of the thickness of the first shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:1; and / or,
[0014] The ratio of the thickness of the second shell layer to the radius of the core of the core-shell quantum dot is 0.4 to 2:1; and / or,
[0015] The ratio of the thickness of the third shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:1.
[0016] Optionally, in some embodiments of the present application, the HOMO energy level of the material of the hole transport layer is -5 eV to -6 eV.
[0017] Optionally, in some embodiments of the present application, the mobility of the material of the hole transport layer is 20×10 -3 ~40×10 -3 cm 2 / Vs.
[0018] Optionally, in some embodiments of the present application, the material of the hole transport layer includes at least one of T5DP2,7 and TBPyS, the structure of T5DP2,7 is shown in formula (I), and the structure of TBPyS is shown in formula (II).
[0019]
[0020] Optionally, in some embodiments of the present application, the light-emitting device further comprises an electron transport layer disposed between the cathode and the light-emitting layer;
[0021] The mobility of the material of the electron transport layer is greater than 0.5×10 -3 cm 2 / Vs, and less than 1×10 -3 cm 2 / Vs.
[0022] Optionally, in some embodiments of the present application, the material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; and / or,
[0023] The average particle size of the material of the electron transport layer is 2 to 12 nm.
[0024] Optionally, in some embodiments of the present application, the core material of the core-shell quantum dots is selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZ At least one of CdS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, At least one of PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, In At least one of NP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or,
[0025] The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or,
[0026] The light emitting device further comprises a hole injection layer disposed between the anode and the light emitting layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenylene]- One or more of: 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tris(diphenylamino)triphenylamine, 4,4',4"-tris(1-naphthyl)-1,1'-biphenyl-4,4"-diamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, and hexaazatriphenylene-capronitrile.
[0027] Optionally, in some embodiments of the present application, the thickness of the anode is 20 to 200 nm; and / or,
[0028] The thickness of the cathode is 40 to 190 nm; and / or,
[0029] The thickness of the hole transport layer is 30 to 180 nm; and / or,
[0030] The thickness of the electron transport layer is 20 to 180 nm; and / or,
[0031] The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, and the thickness of the hole injection layer is 20-200 nm.
[0032] In a second aspect, the present application further proposes a display device, which includes the light-emitting device described above.
[0033] In the technical solution provided in the present application, when the material used in the light-emitting layer is a core-shell structure quantum dot with a well-shell structure, and the light-emitting layer is set as a double-layer film constructed of double-layer quantum dots, the hole mobility of the matching material is greater than or equal to 10×10 -3 cm 2 / Vs, and less than or equal to 100×10 -3 cm 2 / Vs hole transport layer helps to enhance hole injection, overcome the difficulty of external carrier injection in well-shell structure and double-layer film, improve the effective injection and efficient recombination of carriers in the device, improve the injection balance of holes and electrons, and thus improve the efficiency and life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 is a structural schematic diagram of a light-emitting device proposed in one embodiment of the present application;
[0036] Figure 2 Schematic diagram of the band gap structure of a well-structured quantum dot proposed in one embodiment of the present application;
[0037] Reference numerals:
[0038] 100-light-emitting device; 10-anode; 20-light-emitting layer; 30-cathode; 40-electron transport layer; 50-hole transport layer; 60-hole injection layer; 21-quantum dot; 201-core; 202-inner shell; 203-first shell; 204-second shell; 205-third shell. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0040] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".
[0041] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0042] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0043] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0044] In a first aspect, the present application provides a light emitting device 100, which may be a quantum dot light emitting diode (QLED) or the like. Figure 1The light emitting device 100 includes a stacked anode 10, a light emitting layer 20, and a cathode 30, wherein the material of the light emitting layer 20 includes a quantum dot 21 material, and the quantum dot 21 material includes core-shell quantum dots and ligands connected to the surface of the core-shell quantum dots.
[0045] The core-shell quantum dot includes multiple shells, and the multiple shells include adjacent first shells 203, second shells 204, and third shells 205, wherein the band gap of the material of the second shell 204 is smaller than the band gap of the material of the first shell 203, and smaller than the band gap of the material of the third shell 205. Such a shell design allows a well to be formed in the shell of the core-shell quantum dot, so that excess carriers in the device can be stored in the well, which plays a role in extending the exciton fluorescence lifetime and increasing the probability of exciton recombination. However, at the same time, due to the use of a wide-bandgap shell in the well-type shell, it will also cause the problem of relatively more difficult hole injection.
[0046] In some embodiments, the raw material of the ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acid, substituted or unsubstituted C10-C24 chain organic amine, substituted or unsubstituted C10-C24 chain thiol, substituted or unsubstituted C10-C24 chain organic phosphine, substituted or unsubstituted C10-C24 chain organic phosphine oxide, and halide. Wherein, "substituted or unsubstituted" means that the defined group can be substituted or not substituted. When the defined group is substituted, it should be understood that the defined group can be substituted by one or more substituents; the substituent is selected from at least one of C1-C8 alkyl, C1-C8 alkoxy and halogen; optionally, the substituent is selected from at least one of C1-C5 alkyl, C1-C5 alkoxy and halogen; or the substituent is selected from at least one of C1-C3 alkyl, C1-C3 alkoxy and halogen. The halogen refers to -F, -Cl, -Br or -I. Specifically, the organic carboxylic acid includes one or more of decadecanoic acid (CAS: 334-48-5), undecenoic acid (CAS: 112-38-9), tetradecanoic acid (CAS: 544-63-8), oleic acid (CAS: 112-80-1) and stearic acid (CAS: 57-11-4); the organic amine includes one or more of oleylamine (CAS: 112-90-3) and octadecylamine (CAS: 124-30-1); the organic (oxygen) phosphine includes tris(II)-1-butylene glycol (CAS: 112-30-1); One or more of octylphosphine (CAS: 4731-53-7) and trioctylphosphine oxide (CAS: 78-50-2); the thiol includes one or more of n-octylmercaptan (CAS: 111-88-6), dodecanethiol (CAS: 112-55-0) and octadecanethiol (CAS: 2885-00-9); the halide is selected from one or more of hydrofluoric acid, hydrochloric acid, hydroiodic acid, hydrobromic acid, metal fluoride, metal chloride, metal iodide and metal bromide.
[0047] The mass of the ligand accounts for 15% to 20% of the total mass of the quantum dots 21 and the ligand, for example, it can be 15%, 16%, 17%, 18%, 19%, 20% and values between any two of the above values. Within this range, it helps to improve the dispersibility of the quantum dots 21 and enhance its film-forming effect.
[0048] In some embodiments, the ligand includes a first ligand, the raw material of the first ligand is selected from one or more of substituted or unsubstituted C1-C24 chain thiols and halides, the first ligand is a strong coordination ligand, can form a strong coordination bond with the surface cation of the quantum dot 21, is not easy to fall off, and helps to improve the film-forming effect of the light-emitting layer 20. It can be understood that in some embodiments, in addition to the first ligand, the ligand also contains some ligands with relatively weak coordination effects (weak ligands), including but not limited to organic carboxylic acids, organic amines, etc.
[0049] The mass of the first ligand accounts for a percentage greater than 8% and less than 15% of the total mass of the quantum dots 21 and the ligands; for example, it can be 8.1%, 9%, 10%, 11%, 12%, 13%, 14%, 14.9% and values between any two of the above values. When the content of strongly coordinated ligands connected to the surface of the quantum dots 21 decreases, its film-forming property is relatively poor. In view of this, in the embodiment of the present application, the thickness of the light-emitting layer 20 is 1.6 to 2.3 times the average particle size of the quantum dots 21. For example, when the average particle size of the quantum dots 21 used is 10nm and the thickness of the film formed is 16 to 23nm, the obtained film is roughly a double-layer film, that is, Figure 1 As shown, in the thickness direction, the film is roughly formed by two layers of quantum dots 21; by processing the light-emitting layer 20 into a double-layer film, it helps to improve the film quality.
[0050] In the technical solution provided in the present application, when the material used in the light-emitting layer 20 is a core-shell structure quantum dot with a well-type shell structure and a strong coordinating ligand content within 8 to 15%, the light-emitting layer 20 is set to a double-layer film constructed by a double-layer quantum dot 21, which can ensure that the light-emitting layer 20 has a good film-forming effect; at the same time, the tunneling barrier of the carrier is reduced as much as possible, the transmission rate of the carrier is increased, and the recombination efficiency of the carrier is improved.
[0051] Furthermore, in some embodiments, when the anions on the surface of the quantum dot 21 include sulfur atoms, for example, when the quantum dot 21 is CdS or CdZnSe / ZnSe / ZnS / CdZnS / ZnS, and the ligand is a thiol ligand, then when preparing the quantum dot 21, the thiol compound can be added as an anion source, and the S atoms on the ligand can be directly coordinated and connected with the cations on the surface of the quantum dot 21, or directly act as S atoms on the shell surface of the quantum dot 21 and be directly embedded in the shell, which helps to further improve the coordination effect of the ligand and reduce the probability of shedding.
[0052] It can be understood that the content of the ligand and the strong coordinating ligand can be detected by nuclear magnetic resonance and thermal gravimetric test, and the number of strong coordinating ligands on the surface of quantum dot 21 can be introduced during the synthesis process or by ligand exchange. First, nuclear magnetic resonance can measure the content of specific ligands on the surface of quantum dot 21. Secondly, the thermal gravimetric test can determine the total content of ligands on the surface of quantum dot 21. Finally, the difference in ligands between the two is the content of other ligands. The specific test method for determining the content of specific ligands on the surface of quantum dot 21 by nuclear magnetic resonance is as follows: dissolve quantum dot 21 in a deuterated reagent, add a specific amount of internal standard as a reference, and calculate the ratio of the chemical shift integrated area of the ligand of quantum dot 21 to the chemical shift integrated area of the internal standard, so as to quantify the ligand content to be measured. The thermal gravimetric test detection method is as follows: heat the quantum dot 21 material until its mass no longer changes, record the weight loss W1 of the material when it starts to lose weight to the shedding temperature of the strong coordinating ligand, and record the weight loss W2 of the material when it starts to lose weight to the time when its mass no longer changes, then W2 is the content of the ligand, and W2-W1 is the content of the strong coordinating ligand.
[0053] NMR and thermal gravimetric methods can also be used simultaneously, for example: to determine the content of specific quantum dot 21 surface ligands oleic acid (weak ligand) and thiol (thiol as a strong coordinating ligand). The specific test method is as follows: First, dissolve quantum dot 21 in deuterated toluene, use ferrocene as an internal standard (the amount added is rated, the chemical shift is 3.8-4.0ppm), and measure the chemical shift of quantum dot 21 ligand at 5.4-5.8ppm. Finally, divide the integral area of the chemical shift of the ligand at 5.4-5.8ppm by the integral area of the chemical shift of the internal standard at 3.8-4.0ppm to obtain the content of oleic acid ligand. Second, for example: measure the thermal gravimetric loss of quantum dot 21 at 20-600℃, and record the weight loss at 100℃-500℃, which is the total content of ligands on the surface of quantum dot 21. Finally, subtract the oleic acid ligand content from the total ligand content to obtain the thiol ligand content.
[0054] In some embodiments, the fluorescence quantum yield QY of the core-shell quantum dots is ≥ 70%, for example, 70%, 75%, 80%, 85%, 90%, 92%, etc. The quantum dots 21 with higher QY have fewer defects, which helps to reduce the probability of non-radiative recombination. High carrier injection can effectively perform efficient recombination and luminescence in the quantum dot 21 light-emitting layer 20, thereby reducing the probability of device charging and improving device performance.
[0055] In some embodiments, the average particle size of the quantum dots 21 is greater than 8 nm and less than 11 nm. For example, it can be 8.1 nm, 9 nm, 10 nm, 10.5 nm, 10.9 nm, and values between any two of the above. In this way, it is more conducive to the formation of a bilayer film by the quantum dots 21. Correspondingly, the thickness of the light-emitting layer 20 is 13 - 27 nm. For example, it can be 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 20 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, and values between any two of the above.
[0056] In some embodiments, the morphology of the quantum dots 21 includes, but is not limited to, spherical, cubic, tetrahedral, columnar, tetrapod, octapod, flaky, etc.
[0057] In a specific embodiment, in the core-shell quantum dots, the material of the first shell layer 203 includes ZnS, the material of the second shell layer 204 includes CdZnS, and the material of the third shell layer 205 includes ZnS; as Figure 2 shown, the bandgap of the CdZnS shell acts as a well-like structure because it lies between the bandgaps of the adjacent two ZnS shells. Specifically, ZnS is selected for the first shell layer 203 because the ZnS shell has a relatively wide bandgap width and can store excess electrons or holes well as the shell component of the well-like shell layer; Cd x Zn 1-x S(0 < x < 1) shell is selected because this shell layer not only has a relatively wide bandgap itself, but also has a relatively moderate valence band position, which can enhance the binding ability of excitons. And because the overall bandgap of this shell layer is narrower than that of the adjacent ZnS layer, it is very suitable to act as a well-like shell to store excess electrons or holes; ZnS is selected for the third shell layer 205 because this layer has a relatively wide bandgap width and can store excess electrons or holes well as the shell component of the well-like shell layer; in addition, it can also provide a certain exciton binding ability and reduce the influence of external conditions on excitons. In another specific embodiment, in the core-shell quantum dots with a well-like shell layer structure, the material of the first shell layer 203 includes ZnS, the material of the second shell layer 204 includes CdS, and the material of the third shell layer 205 includes ZnS.
[0058] In some embodiments, the core-shell quantum dots have four shell layers. The fourth shell layer can be disposed between the core 201 and the first shell layer 203, or can be disposed outside the third shell layer 205.
[0059] In some embodiments, the core-shell quantum dot has a core 201, and the multiple shells further include an inner shell 202 located between the first shell 203 and the core 201, and the material of the inner shell 202 includes ZnSe. ZnSe has a shallow valence band, which helps to improve hole injection, and its own band gap is relatively moderate. Using it as the material of the inner shell 202 can alleviate the lattice stress of the growth of the first shell 203 to a certain extent. In a specific embodiment, the core-shell quantum dot has four shells, which are the inner shell 202ZnSe, the first shell 203ZnS, the second shell 204CdZnS and the third shell 205ZnS arranged in sequence from the inside to the outside.
[0060] In some embodiments, the ratio of the thickness of the inner shell layer 202 to the radius of the core 201 of the core-shell quantum dot is 0.5 to 2:1; for example, the ratio can be 0.5:1, 0.6:1, 0.8:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.5:1, etc.; this helps to effectively control the binding ability of excitons, which is not only beneficial to reduce the tunneling barrier during carrier injection and promote carrier injection, but also helps to effectively recombine the carriers injected into the core 201 of the quantum dot 21.
[0061] In some embodiments, the ratio of the thickness of the first shell layer 203 to the radius of the core 201 of the core-shell quantum dot is 0.02 to 0.5:1; for example, it can be 0.02:1, 0.025:1, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.45:1, 0.5:1, etc.; it helps to improve the shell layer's ability to store carriers while controlling the barrier for carrier tunneling to the core 201 at a lower level, thereby promoting carrier injection.
[0062] In some embodiments, the ratio of the thickness of the second shell layer 204 to the radius of the core 201 of the core-shell quantum dot is 0.4 to 2:1; for example, the ratio can be 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.3:1, 1.5:1, 1.7:1, 1.8:1, 2:1, etc.; this helps to effectively control the binding ability of excitons and isolate the excitons from the outside world, thereby reducing the probability of excitons being captured by the outside world, while reducing the tunneling barrier during carrier injection and promoting carrier injection.
[0063] In some embodiments, the ratio of the thickness of the third shell layer 205 to the radius of the core 201 of the core-shell quantum dot is 0.02 to 0.5:1; for example, it can be 0.02:1, 0.025:1, 0.03:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.45:1, 0.5:1, etc.; it helps to effectively control the binding ability of excitons and isolate the excitons from the outside world, thereby reducing the probability of excitons being captured by the outside world, while reducing the tunneling barrier during carrier injection and promoting carrier injection.
[0064] In some embodiments, the core 201 material of the quantum dot 21 can be selected from but not limited to at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; as an example, the II-VI compound is selected from but not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgS At least one of Te, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from but not limited to SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe , SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from but not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, A At least one of lPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2.
[0065] As an example, the core-shell structured quantum dots 21 may be selected from but not limited to at least one of CdZnSe / ZnSe / ZnS / CdZnS / ZnS, CdSe / ZnSe / ZnS / CdZnS / ZnS, InP / ZnSe / ZnS / CdZnS / ZnS, CdSeS / ZnSe / ZnS / CdZnS / ZnS, ZnSe / ZnSe / ZnS / CdS / ZnS, and ZnSeTe / ZnSe / ZnS / CdS / ZnS.
[0066] It should be noted that, for the material of the core 201 of the core-shell structure quantum dot or the material of the shell of the core-shell structure quantum dot, the chemical formula provided only indicates the element composition, but does not indicate the content of each element. For example, CdZnS only indicates that it is composed of three elements: Cd, Zn and S. If the content of each element is indicated, it corresponds to Cd x Zn 1-x S, 0 <x<1。
[0067] In some embodiments, the hole transport layer 50 is optimized for the case where the material used in the light-emitting layer 20 is a core-shell structure quantum dot with a well-shell structure, and the light-emitting layer is set as a double-layer film constructed of double-layer quantum dots. Specifically, the mobility of the material of the hole transport layer 50 is greater than or equal to 10×10 -3 cm 2 / Vs, and less than or equal to 100×10 -3 cm 2 / Vs, for example, 10×10 -3 cm 2 / Vs,12×10 -3 cm 2 / Vs,15×10 -3 cm 2 / Vs、18×10 -3 cm 2 / Vs,20×10 -3 cm 2 / Vs,25×10 -3 cm 2 / Vs,30×10 -3 cm 2 / Vs,35×10 -3 cm 2 / Vs,40×10 -3 cm 2 / Vs,50×10 -3 cm 2 / Vs,60×10 - 3 cm 2 / Vs,70×10 -3 cm2 / Vs,80×10 -3 cm 2 / Vs,90×10 -3 cm 2 / Vs,100×10 -3 cm 2 / Vs and values between any two of the above values. In the case where the light-emitting layer 20 is designed as a double-layer film of quantum dots 21 having a well-type structure, a hole transport material with high hole injection can be used to increase hole injection and improve the injection balance of holes and electrons in the device, thereby avoiding the light-emitting layer 20 from being charged and inducing Auger recombination, which in turn affects the life and efficiency of the device.
[0068] Furthermore, in some embodiments, the mobility of the material of the hole transport layer 50 is 20×10 -3 ~40×10 -3 cm 2 / Vs, which helps to further improve the carrier balance.
[0069] In some embodiments, the HOMO energy level of the material of the hole transport layer 50 is -5eV to -6eV; for example, -5eV, -5.2eV, -5.3eV, -5.4eV, -5.5eV, -5.6eV, -5.7eV, -5.8eV, -5.9eV, -6eV and values between any two of the above values.
[0070] Specifically, in some embodiments, the material of the hole transport layer 50 includes at least one of T5DP2,7 and TBPyS.
[0071] T5DP2,7 is derived from the literature “Constructing Effective Hole Transport Channels in Cross-Linked Hole Transport Layer by Stacking Discotic Molecules for High Performance Deep Blue QLEDs”. Its structure is shown in formula (I). Its HOMO level is -5.8 eV. Its hole mobility is 2.6×10 -2 cm 2 / Vs.
[0072] TBPyS is derived from the literature "Benzopyrazine-fused tetracene derivatives: Thin-film formation at the crystalline mesophase for solution-processed hole transporting devices". The structural formula is shown in formula (II), where R is a normal alkyl chain with 8 carbon atoms, i.e. -C8H 17 ; HOMO energy level is -5.18eV; hole mobility is 1.7×10 -2 cm 2 / Vs.
[0073]
[0074] In some embodiments, the light emitting device 100 further includes an electron transport layer 40 disposed between the cathode 30 and the light emitting layer 20. The mobility of the material of the electron transport layer 40 is greater than 0.5×10 -3 cm 2 / Vs, and less than 1×10 -3 cm 2 / Vs, for example, 0.51×10 -3 cm 2 / Vs, 0.6×10 -3 cm 2 / Vs, 0.7×10 -3 cm 2 / Vs, 0.8×10 -3 cm 2 / Vs, 0.9×10 -3 cm 2 / Vs, 0.95×10 -3 cm 2 / Vs, 0.99×10 -3 cm 2 / Vs and values between any two of the above values. Within this range, electron injection can be precisely controlled to improve the injection balance of holes and electrons in the device, thereby preventing the light-emitting layer 20 from being charged and inducing Auger recombination, which in turn affects the life and efficiency of the device.
[0075] In some embodiments, the average particle size of the material of the electron transport layer 40 is 2 to 12 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 11 nm, 12 nm, and values between any two of the above values. The electron transport material with such a particle size is easy to be made into a film with uniform film thickness and dense film during film formation, which helps to improve the film quality.
[0076] In some embodiments, the material of the electron transport layer 40 includes, but is not limited to, one or more of metal oxides and doped metal oxides. As an example, the metal oxide includes, but is not limited to, one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes, but is not limited to, multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes, but is not limited to, one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.
[0077] In addition, in some embodiments, the surface of the electron transport material may be connected with a ligand, and the raw material of the ligand includes one or more of an acid ligand, an amine ligand, and a thiol ligand. Specifically, the ligand includes but is not limited to one or more of oleic acid, oleylamine, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, and octadecanoic acid.
[0078] The metal oxide MO or the doped metal oxide MAO can be obtained by mixing the cation source, the alkali source and the solvent, wherein M is a metal element and A is a doping element. Specifically, when the material to be prepared is a metal oxide, the cation source is a metal salt that can provide the M metal element, such as zinc acetate, etc.; when the material to be prepared is a doped metal oxide, the cation source includes a metal salt that can provide the M metal element and a metal salt that can provide the A doping element, such as zinc acetate, magnesium acetate, etc.; the alkali source includes one or more of an organic base and an inorganic base, the organic base is selected from one or more of hexamethylenetetramine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and urea, and the inorganic base is selected from one or more of sodium hydroxide, lithium hydroxide, potassium hydroxide, calcium hydroxide, ammonium hydroxide, sodium carbonate, and potassium carbonate; the solvent includes alcohols or dimethyl sulfoxide (DMSO). When preparing the electron transport material, the mobility of the electron transport layer 40 material can be precisely controlled by adjusting the type and content of the doping element, the amount of alkali source added, the post-treatment conditions and other parameters. In actual operation, the preparation can be made with reference to the method for regulating the mobility of the electron transport layer 40 material commonly used in the art. Taking the method of regulating the amount of alkali source added to control the electron mobility as an example, in some embodiments, the electron transport layer 40 material is ZnO. In order to adjust its electron mobility, tetramethylammonium hydroxide can be used as the alkali source. When preparing ZnO, the molar ratio of ZnO and tetramethylammonium hydroxide is controlled to be 1:1.5, and a mobility of 0.1×10 -3 cm 2 / Vs ZnO nanoparticles; the molar ratio of ZnO and tetramethylammonium hydroxide can also be controlled to 1:0.5, and a mobility of 5×10 -3 cm 2 / Vs of ZnO nanoparticles.
[0079] In some embodiments, the anode 10 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.
[0080] In some embodiments, the cathode 30 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS. The material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.
[0081] In some embodiments, the light-emitting device 100 further includes a hole injection layer 60 disposed between the anode 10 and the hole transport layer 50, and the material of the hole injection layer 60 includes poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)] (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tri[phenyl One or more of (m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(carbazol-9-yl)triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with tetrafluoro-tetracyano-quinodimethane (F4-TCNQ), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), and hexaazatriphenylene-capronitrile (HAT-CN).
[0082] In some embodiments, the thickness of the anode 10 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.
[0083] In some embodiments, the thickness of the cathode 30 is 40-190 nm; for example, it can be 40-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-190 nm, and the like.
[0084] In some embodiments, the thickness of the hole transport layer 50 is 30 to 180 nm; for example, it can be 30 to 40 nm, 35 to 60 nm, 50 to 80 nm, 55 to 90 nm, 70 to 100 nm, 90 to 120 nm, 110 to 140 nm, 130 to 150 nm, 140 to 170 nm, 160 to 180 nm, and the like.
[0085] In some embodiments, the thickness of the electron transport layer 40 is 20-180 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-180 nm, and the like.
[0086] In some embodiments, the thickness of the hole injection layer 60 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.
[0087] It is understandable that the light emitting device 100 may also be provided with some functional layers conventionally used in the light emitting device 100 to help improve the performance of the light emitting device 100, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc.
[0088] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device.
[0089] Based on the above embodiments, the present application further proposes a method for preparing a light emitting device 100, which is used to prepare the above light emitting device 100. In some embodiments, the light emitting device 100 may be a positive light emitting device, and accordingly, the preparation method includes:
[0090] S10a, providing an anode 10;
[0091] S20a, sequentially disposing a hole functional layer, a light emitting layer 20 and an electron transport layer 40 on the anode 10;
[0092] S30 a , disposing the cathode 30 on the electron transport layer 40 .
[0093] In some other embodiments, the light emitting device 100 may be an inverted light emitting device, and accordingly, the preparation method includes:
[0094] S10b, providing a cathode 30;
[0095] S20b, sequentially disposing an electron transport layer 40, a light emitting layer 20 and a hole functional layer on the anode 10;
[0096] S30b, disposing the anode 10 on the electron transport layer 40 .
[0097] In steps S20a and S20b, the hole functional layer includes the hole transport layer 50 , or includes the hole transport layer 50 and the hole injection layer 60 . When the hole functional layer includes the hole transport layer 50 and the hole injection layer 60 , the hole injection layer 60 is disposed closer to the anode 10 .
[0098] In the preparation method of the light-emitting device 100, the preparation method of the anode 10, the light-emitting layer 20, the electron transport layer 40, the hole transport layer 50, the hole injection layer 60 and the cathode 30 can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical plating and solution method, among which the physical plating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip pulling, immersion, spraying, roll coating, casting, slit coating, and strip coating.
[0099] The materials of the anode 10 , the light emitting layer 20 , the electron transport layer 40 , the hole transport layer 50 , the hole injection layer 60 and the cathode 30 are as described above and will not be described in detail here.
[0100] In some embodiments, after the light emitting device 100 is prepared, the step of packaging the light emitting device 100 is further included. The packaging process can be performed by a common machine packaging or by manual packaging. Preferably, in the environment of the packaging process, the oxygen content and the water content are both less than 0.1 ppm to ensure the stability of the light emitting device 100.
[0101] In addition, the present application also relates to a display device, which includes the light-emitting device 100. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0102] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.
[0103] Example 1
[0104] This example aims to investigate the effect of the number of quantum dot layers on device performance
[0105] Experimental Group 1
[0106] The structure of the QLED device in this experimental group is: anode, hole injection layer, hole transport layer, quantum dot light-emitting layer, electron transport layer and cathode stacked from bottom to top. The thickness of each layer is: anode 140nm, hole injection layer 120nm, hole transport layer 80nm, quantum dot light-emitting layer 20nm, electron transport layer 50nm, cathode 50nm.
[0107] (1) A glass substrate is provided, and ITO is evaporated on the glass substrate to form an anode.
[0108] (2) Spin coating a PEDOT:PSS material (a commercial product with a doping ratio of 1:6 and a solute content of 1.5 wt%) on the anode and heating at 150° C. for 15 min to obtain a hole injection layer.
[0109] (3) The substrate prepared in step (2) was transferred to a nitrogen atmosphere, and a hole transport material was spin-coated on the hole injection layer, and heated at 150° C. for 15 min to obtain a hole transport layer; wherein the hole transport material was T5DP2,7, whose HOMO energy level was −5.8 eV and whose mobility was 2.6×10 -3 cm 2 / Vs.
[0110] (4) Spin coating an octane solution of a quantum dot material on the hole transport layer, and heating at 80° C. for 10 min to obtain a quantum dot light-emitting layer; wherein the quantum dot material is red quantum dots CdZnSe / ZnSe / ZnS / CdZnS / ZnS, with a QY of 80%, an average particle size of 10 nm, a surface ligand of octanethiol, a mass content of octanethiol on the surface of the quantum dots of 10%, and a ratio of the thickness of the inner shell layer ZnSe to the core radius of 1:1, a ratio of the thickness of the first shell layer ZnS to the core radius of 0.2:1, a ratio of the thickness of the second shell layer CdZnS to the core radius of 1.5:1, and a ratio of the thickness of the third shell layer ZnS to the core radius of 0.2:1; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the octane solution of the quantum dot material is 17 mg / ml, so as to control the quantum dot light-emitting layer to be a double-layer film.
[0111] (5) An electron transport layer is prepared on the quantum dot light-emitting layer; wherein, 0.85 mmol of Zn(Ac)2·2H2O, 0.15 mmol of Mg(Ac)2·4H2O and 10 ml of DMSO are weighed and placed in a three-necked flask, and then stirred at 25°C until completely dissolved to obtain a first solution; 1.5 mmol of tetramethylammonium hydroxide is dissolved in 10 ml of ethanol to obtain a second solution; then the second solution is slowly added dropwise to the first solution; after the reaction is completed, ethyl acetate is added thereto for precipitation, centrifuged, and the supernatant is discarded; anhydrous ethanol is added to dissolve, and then ethyl acetate is added for precipitation and centrifugation. Repeat the above steps twice to obtain ZnMgO nanoparticles. The ZnMgO nanoparticles are dispersed in ethanol, spin-coated on the light-emitting layer to form a solid film, and then placed in an oxygen atmosphere and UV-treated for 5 min at 365 nm and 1200 W to obtain an electron mobility of 0.8×10 -3 cm 2 / Vs ZnMgO electron transport layer.
[0112] (6) Placing the substrate obtained in step (5) in a vapor deposition chamber, vapor-depositing Ag on the electron transport layer to obtain a cathode, and encapsulating to obtain a QLED device.
[0113] Control group 1
[0114] The scheme of control group 1 is basically the same as that of experimental group 1, except that in this control group, the quantum dot luminescent layer is a double-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 10 nm; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 9 mg / ml, so as to control the quantum dot luminescent layer to be a single-layer film. The other steps and parameters are the same as those of experimental group 1.
[0115] Control group 2
[0116] The scheme of control group 2 is basically the same as that of experimental group 1, except that in this control group, the quantum dot luminescent layer is a four-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 10 nm; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 30 mg / ml, so as to control the quantum dot luminescent layer to be a four-layer film. The other steps and parameters are the same as those of experimental group 1.
[0117] (i) Take the semi-finished device obtained in step (4) during the preparation of experimental group 1, control group 1 and control group 2, wherein the top layer of the semi-finished device is the light-emitting layer. The roughness of the light-emitting layer is examined by AFM to evaluate its film-forming effect, and the results are recorded in Table 1.
[0118] (ii) Prepare the corresponding single carrier devices of experimental group 1, control group 1 and control group 2 respectively, and test the current density-voltage curve of the single carrier transport thin film device (HOD / EOD). Take the current density of the device at 4V for comparison. Where:
[0119] The preparation method of the single electron device (EOD) is basically the same as the preparation method of its corresponding complete QLED device, the only difference is that the hole injection layer and the hole transport layer are subtracted.
[0120] The preparation method of the single hole device (HOD) is basically the same as the preparation method of its corresponding complete QLED device, the only difference is that the electron transport layer is subtracted.
[0121] The results are recorded in Table 1.
[0122] (III) Take the devices made in experimental group 1, control group 1 and control group 2, and place the devices under 120°C for 15 minutes for heat treatment to accelerate the forward aging of the devices. Then, perform subsequent performance tests on the devices after the heat treatment, and record the results in Table 1. The detection method is as follows:
[0123] (1) The detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electrophotoelectric devices and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:
[0124]
[0125] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.
[0126] Test conditions: carried out at room temperature, air humidity is 30-60%.
[0127] (2) The test method for life T95@1000nit is:
[0128] The time required for the device to reduce its brightness to a certain percentage of the maximum brightness when driven by a constant current or voltage. The time it takes for the brightness to drop to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life under 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:
[0129]
[0130] Among them, T95L is the lifespan at low brightness, T95H is the measured lifespan at high brightness, LH is the device accelerated to the maximum brightness, LL is 1000nit, and A is the acceleration factor. This experiment measured the lifespan of several groups of red QLED devices at rated brightness and obtained an A value of 1.7.
[0131] Table 1
[0132]
[0133] It can be seen from the above table:
[0134] The film quality of control group 1 is poor, which is manifested by the large leakage current of EOD device and HOD device, while both experimental group 1 and control group 2 have good roughness. At the same time, experimental group 1 has better EQE and T95@1000nit than control group 2, and its HOD device and EOD device have not only large current density at 4V, but also close current density, indicating that the preparation of double-layer film can improve the film quality while improving the efficiency and life of the device. It shows that when the luminescent layer material adopts core-shell structure quantum dots with QY greater than or equal to 70% and a well-shell structure, and the hole transport layer adopts high hole injection (greater than 10×10 - 3 cm 2 / Vs, and less than 100×10 -3 cm 2 / Vs) hole transport material, and the electron transport layer adopts a medium conduction band (greater than 0.5×10 - 3 cm 2 / Vs, and less than 1×10 -3 cm 2 / Vs) electron transport material, compared with single-layer or multi-layer films, the double-layer film quantum dot light-emitting layer has more balanced carrier injection and exhibits a significantly longer service life. This shows that the double-layer film is more compatible with the above-mentioned design, which helps to significantly improve the life of the device while ensuring the luminous efficiency.
[0135] Example 2
[0136] This example aims to investigate the effect of the quantum dot shell structure on device performance.
[0137] The schemes of experimental group 2 and control groups 2 to 4 are basically the same as those of experimental group 1, with the only difference being that in each control group, the quantum dot materials used in the quantum dot light-emitting layer are changed to the materials listed in Table 2 below.
[0138] Performance tests were performed on experimental groups 1-2 and control groups 2-4, and the results are recorded in Table 2.
[0139] Table 2
[0140]
[0141] It can be seen from the above table that for devices using the same hole transport layer and electron transport layer design, when the shell structure of the quantum dot light-emitting layer material is changed from the well structure ZnSe / ZnS / CdZnS / ZnS or the well structure ZnSe / ZnS / CdS / ZnS to other non-well shell structures, the device life is greatly reduced. This shows that compared with other shell structures, the well shell structure design is better matched with the device hole transport layer and electron transport layer.
[0142] Example 3
[0143] This example aims to investigate the effect of quantum dot shell thickness on device performance.
[0144] This embodiment also sets up control groups 5 to 8. Among them:
[0145] The schemes of control groups 5 to 8 are basically the same as those of experimental group 1, with the only difference being that in each control group, the quantum dot material used in the quantum dot light-emitting layer is changed to the material with the thickness of each shell layer defined in Table 3 below.
[0146] Performance tests were performed on experimental group 1 and control groups 5 to 8, and the results are recorded in Table 3.
[0147] Table 3
[0148]
[0149] It can be seen from the table above that with the change of the thickness of each shell layer, the EQE and T95 of each group of devices 1000nit There has been a significant change. For the well-shell quantum dots with a shell structure of ZnSe / ZnS / CdZnS / ZnS in the double-layer quantum dot luminescent layer, the thickness of the well-shell layer plays an important role in the efficient injection of electrons and holes into the quantum dot core; further, compared with the control groups 5-8, the experimental group 1 showed higher EQE and T95 1000nit , indicating that the shell thickness design scheme proposed in this application is better and significantly improves the EQE and life of the device.
[0150] Example 4
[0151] This example aims to investigate the effect of hole transport materials on device performance.
[0152] This embodiment also sets up experimental group 3, experimental group 4, and control groups 9 to 11. Among them:
[0153] The experimental group or control group scheme is basically the same as that of experimental group 1, except that in each experimental group or control group, the hole transport material used in the hole transport layer is changed to the material in Table 4 below.
[0154] Performance tests were performed on experimental groups 1, 3, 4 and control groups 9-11, and the results are recorded in Table 4.
[0155] Table 4
[0156]
[0157]
[0158] It can be seen from the above table that the experimental group exhibits higher luminous efficiency and lifespan than the control group, indicating that the materials provided by the experimental group are more compatible with the device provided in this embodiment than the four materials provided by the control group. Obviously, for the single-layer film luminescent layer prepared by using quantum dots with QY greater than or equal to 70% and shell layers of ZnSe / ZnS / CdZnS / ZnS, and the electron mobility of the material is greater than 0.5×10 -3 cm 2 / Vs, and less than 1×10 -3 cm 2 / Vs for the device with electron transport layer, the hole mobility of the hole transport material used is greater than 10×10 -3 cm 2 / Vs, and less than 100×10 -3 cm 2 / Vs, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.
[0159] Example 5
[0160] This example aims to investigate the effect of the mobility of the electron transport material on the device performance.
[0161] This embodiment further sets up a control group 12 and a control group 13. Among them:
[0162] The control group scheme is basically the same as the experimental group 1, the only difference is that in each control group, the electron transport material used in the electron transport layer is changed to the material in the following Table 5.
[0163] The mobility is 0.01×10 -3 The preparation method of the ZnMgO electron transport layer is as follows: weigh 0.9mmol of Zn(Ac)2·2H2O, 0.1mmol of Mg(Ac)2·4H2O and 10ml of DMSO into a three-necked flask, and then stir at 25°C until completely dissolved to obtain a first solution; dissolve 1.5mmol of tetramethylammonium hydroxide in 10ml of ethanol to obtain a second solution; then slowly add the second solution to the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain a mobility of 0.01×10 -3 The ZnMgO nanoparticles were dispersed in ethanol to prepare an ethanol solution of ZnMgO nanoparticles with a concentration of 30 mg / ml, which was spin-coated on the light-emitting layer and heated at 100°C for 8 minutes to form an electron transport layer.
[0164] The mobility is 2×10 -3 The preparation method of the ZnO electron transport layer is as follows: weigh 1mmol of Zn(Ac)2·2H2O and 10ml of DMSO into a three-necked flask, and then stir at 25°C until completely dissolved to obtain a first solution; dissolve 0.8mmol of tetramethylammonium hydroxide in 10ml of ethanol to obtain a second solution; then slowly add the second solution to the first solution; after the reaction is completed, add ethyl acetate to precipitate, centrifuge, and discard the supernatant; add anhydrous ethanol to dissolve, and then add ethyl acetate to precipitate and centrifuge. Repeat the above steps twice to obtain an electron mobility of 2×10 -3 cm 2 / Vs ZnO nanoparticles. An ethanol solution of ZnO nanoparticles with a concentration of 30 mg / ml was spin-coated on the quantum dot light-emitting layer and heated at 100°C for 8 minutes to obtain an electron transport layer.
[0165] Performance tests were performed on experimental group 1, control group 12 and control group 13, and the results are recorded in Table 5.
[0166] Table 5
[0167]
[0168] As can be seen from the above table, compared with the control group, the experimental group exhibits higher luminous efficiency and lifespan, indicating that compared with the material provided by the control group, the electron transport material provided by the experimental group is more compatible with the device provided in this embodiment. Obviously, for the double-layer film luminescent layer prepared by using quantum dots with QY greater than or equal to 70% and shell layers of ZnSe / ZnS / CdZnS / ZnS, and the material with hole mobility greater than 10×10 -3 cm2 / Vs, and less than 100×10 -3 cm 2 For devices using hole transport materials with a hole transport layer of 0.5 × 10 / Vs, the electron transport material used is an electron transport material with an electron mobility greater than 0.5 × 10 -3 cm 2 / Vs, and less than 1×10 -3 cm 2 / Vs, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.
[0169] The light-emitting device and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A light emitting device, characterized in that: It comprises an anode, a hole transport layer, a light-emitting layer, and a cathode which are stacked in sequence, wherein the material of the light-emitting layer comprises core-shell quantum dots, the core-shell quantum dots comprise a plurality of shell layers, the plurality of shell layers comprise adjacent first shell layers, second shell layers, and third shell layers, wherein the band gap of the material of the second shell layer is smaller than the band gap of the material of the first shell layer, and smaller than the band gap of the material of the third shell layer, and the thickness of the light-emitting layer is 1.6 to 2.3 times the average particle size of the core-shell quantum dots; The mobility of the material of the hole transport layer is greater than 10×10 -3 cm 2 / Vs, and less than 100×10 -3 cm 2 / Vs.
2. The light emitting device according to claim 1, characterized in that: The fluorescence quantum yield of the core-shell quantum dots is greater than or equal to 70%; and / or, The average particle size of the core-shell quantum dots is greater than 8 and less than 11 nm; and / or, The material of the first shell layer includes ZnS, the material of the second shell layer includes CdZnS, and the material of the third shell layer includes ZnS; and / or, The core-shell quantum dot has a core, and the plurality of shell layers further include an inner shell layer located between the first shell layer and the core, and the material of the inner shell layer includes ZnSe.
3. The light emitting device according to claim 2, characterized in that: The ratio of the thickness of the inner shell layer to the radius of the core of the core-shell quantum dot is 0.5 to 2:1; and / or, The ratio of the thickness of the first shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:1; and / or, The ratio of the thickness of the second shell layer to the radius of the core of the core-shell quantum dot is 0.4 to 2:1; and / or, The ratio of the thickness of the third shell layer to the radius of the core of the core-shell quantum dot is 0.02 to 0.5:
1.
4. The light emitting device according to claim 1, characterized in that: The HOMO energy level of the material of the hole transport layer is -5 eV to -6 eV.
5. The light emitting device according to claim 1, characterized in that: The mobility of the material of the hole transport layer is 20×10 -3 ~40×10 -3 cm 2 / Vs.
6. The light emitting device according to claim 5, characterized in that: The material of the hole transport layer includes at least one of T5DP2,7 and TBPyS. The structure of T5DP2,7 is shown in formula (I), and the structure of TBPyS is shown in formula (II).
7. The light emitting device according to claim 1, characterized in that: The light emitting device further comprises an electron transport layer disposed between the cathode and the light emitting layer; The mobility of the material of the electron transport layer is greater than 0.5×10 -3 cm 2 / Vs, and less than 1×10 -3 cm 2 / Vs; and / or, The material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping element includes one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu; and / or, The average particle size of the material of the electron transport layer is 2 to 12 nm.
8. The light emitting device according to claim 1, characterized in that: The core material of the core-shell quantum dots is selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, Cd At least one of ZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, Pb At least one of SeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, I At least one of nNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; and / or, The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or, The light emitting device further comprises a hole injection layer disposed between the anode and the light emitting layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenylene]- One or more of: 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tris(diphenylamino)triphenylamine, 4,4',4"-tris(1-naphthyl)-1,1'-biphenyl-4,4"-diamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, and hexaazatriphenylene-capronitrile.
9. The light emitting device according to claim 7, characterized in that: The thickness of the anode is 20 to 200 nm; and / or, The thickness of the cathode is 40 to 190 nm; and / or, The thickness of the hole transport layer is 30 to 180 nm; and / or, The thickness of the electron transport layer is 20 to 180 nm; and / or, The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, and the thickness of the hole injection layer is 20-200 nm.
10. A display device, characterized in that: The display device comprises the light emitting device according to any one of claims 1 to 9.
